Blockade of Exosome Release Sensitizes Breast Cancer to Doxorubicin via Inhibiting Angiogenesis - Jindi He; Fengyi He; Qinlian Yang; Qiuyun Li (Cancer Medicine)
ABSTRACT Background Chemotherapy combined with angiogenesis inhibition holds great promise in improving the therapeutic efficacy in cancer treatment. The aim of this study was to explore the effect of exosome blockade on tumor angiogenesis and chemotherapy efficacy. Methods Exosomes were extracted by ultracentrifugation, and the effect of exosomes on angiogenesis was evaluated by 4T1 mouse breast cancer cell line and the syngeneic mouse tumor model and immunofluorescence. The endocytosis of exosomes from vascular endothelial cells was evaluated in vitro by co‐culture and immunofluorescence assays. Tube formation and CCK‐8 assays were used to evaluate the effect of exosomes on angiogenesis in vitro. The effect of exosome blockade on the efficacy of doxorubicin was evaluated by 4T1 mouse breast cancer model, cancer cell‐derived exosomes (Exo4T1), GW4869 and doxorubicin in vivo. Results Exo4T1 can be efficiently endocytosed by vascular endothelial cells both in vitro and in vivo. Within the recipient endothelial cells, Exo4T1 elicited angiogenesis at least partially via promoting cell proliferation, as the exosomes were carrying cargos with pro‐proliferation capacity. Blockade of exosome release through GW4869 significantly inhibited angiogenesis, increased the concentration of doxorubicin within the tumor, and sensitized the tumor to doxorubicin in the murine 4T1 syngeneic model, whereas the therapeutic effects were abrogated when Exo4T1 was additionally treated. Moreover, we found there was no synergy between GW4869 and pazopanib (PP, a traditional angiogenesis inhibitor). Conclusions Together, we here revealed that cancer‐derived exosomes promote angiogenesis during cancer progression and GW4869 treatment would sensitize the cancer cells to doxorubicin at least partially via inhibiting angiogenesis.